The Islamic Economic Perspective on Branchless Banking - Fitria Asas; Muhyidin Muhyidin (Journal of Business Improvement, 2024)
Bank Indonesia (BI) launched Branchless Banking, also known as Non-Branch Banking Services. In other words, Branchless Banking offers limited payment services not conducted at a bank's physical office. This study aims to enhance financial inclusion by reaching people living in remote areas or those without easy access to physical bank branches. Branchless Banking has great potential to improve financial inclusion and provides conventional banks broader access to the population, especially in remote regions. Branchless Banking can deliver financial services that are easy, fast, and effective, supporting the principles of justice, transparency, and mutual benefit, which are essential in every Islamic economic transaction